Trophic State of The Lubuk Siam Lakes, Siak Hulu District, Kampar RegencyBased on The TSI (Trophic State Index) - Rensi Adolina Damanik; Clemens Sihotang; Madju Siagian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract            TSI is one of methods used to determine the trophical state of waters. The TSI was calculated  based on physical, chemical and biological parameters and it is more representative for analyzing the trophical state of waters.This research was conducted in February-March 2017 and it aims to understand the trophic state of the Lubuk Siam lake.  There were three sampling stations namely Station 1 (inlet), Station 2 (pen cage area ), and Station 3 (outlet). In each station, there were three sampling points, in the surface (50 cm), 2 secchi depth (150 cm) and 3 secchi depth (220 cm). Samplings were done once/week for 3 weeks period. Water quality parameter measured were chlorophyll-a, total phosphorus, transparency, temperature, pH, nitrate, and free carbondioxide. Trophic status was calculated based on Carlson’s Trophic State Index (TSI). Result  shown that the transparency was 63-89cm, totalphosphorus 0.01–0.23 mg/L, chlorophyll-a 10.27-72.52µg/L, depth 300-700 cm, temperature 27.6-31.1 oC, pH 6.7-7.5dissolved oxygen 4.098-8.264 mg/L,free carbondioxide 3.902 – 15.981mg/L andnitrate 0.054-0.241 mg/L. Based on Carlson’s TSI value, the Lubuk Siam Lake can be categorized as mesotrophic to light eutrophic. Keywords : Lubuk Siam, Lakes, TrophicState Index, Water Quality